Menghadapi Quarter Life Crisis: Peran Konseling Islam dalam Ketahanan Mental dan Spiritual - Ilman, Hadhar; Nurjannah, Nurjannah (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This research aims to examine the role of Islamic counseling in overcoming Quarter Life Crisis (QLC) and increasing the mental and spiritual resilience of individuals. The research used a qualitative approach with a literature study method, combining findings from the fields of Islamic psychology and faith-based counseling. The results showed that QLC, which is commonly experienced by individuals aged 18-29, can impair mental and spiritual well-being. Internal factors such as childhood experiences and external factors such as family support play an important role. Islamic counseling, with spiritual principles such as tawakal and ikhlas as well as dhikr practices, proved effective in providing emotional support and strengthening mental resilience in the face of life's uncertainties. This approach helps individuals manage anxiety, indecision and life stress through strengthening religious and psychological values. This research is expected to contribute to developing a holistic Islamic counseling approach, as well as providing practical guidance for counselors and individuals facing QLC